(untitled) (Anclajes, 2024)
In Los Recuerdos del Porvenir, Elena Garro addresses the problematic Mexican sociocultural situation through the female type of the cuscas, or young prostitutes, victims of violence naturalized as an ideological format. This article presents a reading of the novel’s models of literal and symbolic violence through the work of Philippe Bourgois, Pierre Bourdieu, Johan Galtung and Nancy Scheper-Hughes. The representation of these fictional characters in Garro’s novel shows how structural violence permeates social relations through a network of prejudices and systems of oppression that prevent the cuscas’ liberation. The characteristics given to the prostitutes in the novel articulate an argument about national identity, which for the author present a potential to define the future. The article concludes by confirming Garro’s literature as a committed political activity, due to its critical position in the face of any social discrimination and the revaluation of the sectors neglected by power.